Bankruptcy in an Industrial Society : A History of the Bankruptcy Court for the Northern District of Ohio - Murnane, M. Susan, 1951- (Book collections on Project MUSE., 2014)
Not a history of bankruptcy law, Murnane's work is a social and institutional history of the Bankruptcy Court for the Northern District of Ohio. The work explains the development of the court and the story of the people who worked there and of those who sought refuge in the bankruptcy court, within the context of northern Ohio's changing economy. The story of this particular bankruptcy court also illustrates the historical evolution of bankruptcy as an American institution.